Balanced nutrient stoichiometry of organic amendments enhances carbon priming in a poorly structured sodic subsoil. (June 2020) - Fang, Yunying; Singh, Bhupinder Pal; Farrell, Mark; Van Zwieten, Lukas; Armstrong, Roger; Chen, Chengrong; Bahadori, Mohammad; Tavakkoli, Ehsan
Abstract: Application of organic amendments (OAs), nutrients and gypsum to sodic subsoils is of great interest to improve soil functionality and crop yield. However, controversy remains about the impact of the priming effect (PE) on native soil organic carbon (SOC), and the mechanisms governing the dynamics of the PE by OAs (with variations in nutrient stoichiometry). To address these gaps in knowledge, this nine-month study applied C4 -plant-derived OAs in a C3 -plant-derived soil at 6.2 g C kg −1 soil, with and without the exogenous supply of nutrients (nitrogen and/or phosphorus) or gypsum. Across the treatments, the cumulative PE was between 135 and 475 mg CO2 –C kg −1 soil over the nine months, equivalent to 2.3–8.2% of native SOC loss. In the first two months, the positive PE by the OAs could be attributed to co-metabolism and nitrogen (N) mining. These theories were supported by (i) the enhanced growth of microbial biomass associated with increased soil labile C (such as dissolved organic C); and (ii) the decreased soil mineral N availability, likely via microbial N immobilization, particularly with the inputs of sorghum stubble or sugarcane bagasse. Towards the end of the incubation, the relative PE (i.e ., PE ÷ SOC mineralization in the control soil) was higher in the OA treatments (sorghum stubble and sugarcane bagasse) where nutrients were added to lower the C: nutrient stoichiometric ratios. These results support the theory of microbial stoichiometric decomposition of SOC, which may have become the dominant mechanism of PE over time. The application of gypsum, together with OAs (sorghum stubble or sugarcane bagasse), did not significantly change the magnitude or direction of the PE. In conclusion, the significant native SOC losses and N immobilization induced by the OAs, particularly where we balanced the nutrient stoichiometric ratios, indicate the vulnerability of subsoil SOC, and hence the potential of C sequestration in a sodic subsoil following the application of OAs may be limited. Graphical abstract: Image 1 Highlights: Labile C in OAs controlled the positive priming effect (PE) in the first 2-months. Extra nutrients in OAs increased the magnitude of the PE after 2-months. The PE was negatively related to soil mineral N availability, suggesting N mining. Gypsum did not alter the magnitude of the PE by OAs in the sodic subsoil.